STUDI PRODUKTIVITAS DAN RENDEMEN INDUSTRI PENGGERGAJIAN KAYU AKASIA DAUN LEBAR (Acacia mangium Willd) DI KECAMATAN LANDASAN ULIN KOTA BANJARBARU KALIMANTAN SELATAN - Rosidah R Radam (Jurnal Hutan Tropis, 2011)
The activity of sawmill have been long enough done by local society because very assistive and add production socialize, some of owner of bandsaw/sawmill also make this effort as effort remain to and there is also making it as effort peripheral.  Intention of this research is to know industrial and rendemen productivity of sawmill of acacia wide leaf wood (Acacia mangium Willd).  The method that being used is method of direct measurement and observation in industrial location of sawmill of acacia wide leaf wood and method of direct interview and also record data that related to this research.  The analyse data is productivity calculation, rendemen and waste.  Productivity mean of industrial sawmill of acacia wide leaf wood is equal to 6,38 m3/day or 0,0160 m3/hours. Rendemen mean of industrial sawmill of acacia wide leaf wood is equal to 80,011%.  Mean of industrial disposal of sawmill of acacia wide leaf wood is equal to 19,99% (1,62 m3), this matter is caused by a quality wood of good Acacia (not many experiencing of handicap of wood).  From result of research suggested to conduct research of continuation hit influence of other factor to productivity and rendemen at acacia wide leaf wood sawmill like age, environmental work (arrange situation), and the worker education.Keyords :  productivity, rendemen, waste, sawmill, acacia wide leaf wood (Acacia mangium Willd)